Optical characteristics of graphene oxide film and its application in planar waveguide devices / Lim Weng Hong - Lim, Weng Hong (2016)

(untitled)
Investigation of the optical characteristics of Graphene Oxide (GO) film was carried out. The GO film was fabricated by drop-casting of GO solution onto a planar substrate. The GO solution was prepared using improved Hummer’s method. The optical conductivity of GO film for TE-polarised light (perpendicular to the stacking axis of GO layers) is in the magnitude of ~103 Sm-1, which results in very high optical absorption. On the other hand, TM-polarised light will encounter relatively smaller absorption due to a much lower optical conductivity. It was also observed that the conductivity of the GO film is affected by the amount of water molecule present in the film. Water molecules are able to permeate in and out of the GO film freely due to the film natural properties. The permeated water molecules readily interact with the functional groups of each individual GO layer and this interaction reduces the film conductivity by further widening its bandgap. This process was reversible when the water content in the film was reduced. In addition, photothermal reduction through optical phonon relaxation of GO film using near infrared light source was studied. A numerical model of wave propagation in GO film was then developed followed by experimental verification of the model. The GO film was then coated onto a planar optical waveguide. Strong polarisation effect was observed due to the large anisotropy complex dielectric function of GO film. The GO film functionalized waveguide polariser showed a broad band response over the visible and near infrared wavelength range with a maximum polarisation extinction ratio of more than 40 dB in the 1550 nm optical fibre communication window. The response of GO film to changing water content has also been applied in optical water detection and humidity sensing. Finally, by exploring the reversible photothermal reduction characteristics of GO film, an all-optical GO-based waveguide modulator with a modulation depth of 72% and response time of <100 ms was demonstrated.